2010
DOI: 10.1094/cchem-87-3-0175
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Physical, Compositional, and Wet‐Milling Characteristics of the F1 Generation of Corn Hybrids of Introgressed Exotic and Adapted Inbred Lines

Abstract: Hybrids with high grain yield and higher starch, protein, or oil content are available to corn growers; however, they result from crossing adapted Corn Belt inbred lines that rarely include exotic germplasm. This study was conducted to determine whether Corn Belt lines introgressed with exotic materials from Argentina, Chile, Uruguay, Cuba, and Florida have appropriate wet‐milling characteristics in their hybrids. Ten lines from the Germplasm Enhancement of Maize (GEM) project with different starch contents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
13
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 15 publications
8
13
3
Order By: Relevance
“…FAUAS‐437 and FAUAS‐387 exhibited a significantly higher TW ( P < 0.05) than other genotypes (Table I). Our results were within the range (mean value of 77.6 kg/hL) of GEM lines with exotic material introgressed reported by Taboada‐Gaytan et al (2010b) and Singh et al (2001) for 51 exotic accessions used in the GEM project (mean value of 79.3 kg/hL) but were slightly lower than those of experimental hybrids with exotic material introgressed (72.98–84.06 kg/hL) reported by Taboada‐Gaytan et al (2010a). TW has been an important and useful qualitative property in determining maize grades and selling price (Paulsen et al 2003).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…FAUAS‐437 and FAUAS‐387 exhibited a significantly higher TW ( P < 0.05) than other genotypes (Table I). Our results were within the range (mean value of 77.6 kg/hL) of GEM lines with exotic material introgressed reported by Taboada‐Gaytan et al (2010b) and Singh et al (2001) for 51 exotic accessions used in the GEM project (mean value of 79.3 kg/hL) but were slightly lower than those of experimental hybrids with exotic material introgressed (72.98–84.06 kg/hL) reported by Taboada‐Gaytan et al (2010a). TW has been an important and useful qualitative property in determining maize grades and selling price (Paulsen et al 2003).…”
Section: Resultssupporting
confidence: 91%
“…Zehr et al (1995) compared the wet‐milling properties among adapted inbred lines. The wet‐milling characteristics of GEM accessions (Singh et al 2001), GEM lines (Taboada‐Gaytan et al 2009), and experimental maize hybrids with exotic and nonexotic origin (Taboada‐Gaytan et al 2010a, 2010b) have also been reported. Efforts conducted to study Mexican blue maize landraces are currently focused on the evaluation of their anthocyanin content (Salinas‐Moreno et al 2012), antioxidant capacity (Del Pozo‐Insfran et al 2006), and more recently their structural, morphological, physicochemical, functional, and technological properties and starch biosynthesis enzymes (Agama‐Acevedo et al 2005, 2011; Utrilla‐Coello et al 2009; De la Rosa‐Millán et al 2010).…”
mentioning
confidence: 99%
“…Earlier, we reported on the dynamics of LYS, MET, and CYS and their relationships with protein and other phytochemicals in the maize kernel ( Jaradat and Goldstein, 2013) and provided multivariate statistical evidence at different hierarchical levels, including HGEs, populations, and accessions within populations, indicating that the nutritional quality of maize kernels is influenced by many factors, including genetic background of endosperm texture, inbreeding level, phytochemical composition, and the direct and indirect interactions between and within physicochemical traits. The current study provided in-depth analyses and interpretation of results beyond what can be gleaned, for example, from classical assessment of protein content and its nutritional quality as described by amino acid composition (Fufa et al, 2003), phenotypic characterization of quality protein endosperm as described by desirable combinations of high amino acid content and endosperm vitreousness (Gutierrez-Rojas et al, 2008), or physical and compositional characterization of hybrids between exotic and adapted maize lines as described by test weight, thousand kernel weight, absolute density, and starch, protein, and oil contents (Taboada-Gaytan et al, 2010). The current study provided in-depth analyses and interpretation of results beyond what can be gleaned, for example, from classical assessment of protein content and its nutritional quality as described by amino acid composition (Fufa et al, 2003), phenotypic characterization of quality protein endosperm as described by desirable combinations of high amino acid content and endosperm vitreousness (Gutierrez-Rojas et al, 2008), or physical and compositional characterization of hybrids between exotic and adapted maize lines as described by test weight, thousand kernel weight, absolute density, and starch, protein, and oil contents (Taboada-Gaytan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We formulated latent variable models (Table 12) on the basis of past experience and theoretical knowledge of intercorrelated data in the maize kernel (Seebauer et al, 2010;Taboada-Gaytan et al, 2010;Jaradat and Goldstein, 2013) and were able to test multivariate hypotheses about the causal relationships among multiple variables using SEM (Lamb et al, 2011). The standardized path coefficients were useful for comparisons of the relative strengths of the paths; they can be interpreted as the change in standard deviation units expected in the dependent variable with a change in the independent variable (Grace et al, 2010).…”
Section: Causal Multiple Amino Acid Relationshipsmentioning
confidence: 99%
“…The U.S. successor to LAMP, Germplasm Enhancement of Maize (GEM) (Pollak 2003;Salhuana and Pollak 2006), enhances useful exotic germplasm to diversify the U.S. hybrid corn germplasm base. This germplasm also provides opportunity to impact starch traits (Singh et al 2001a(Singh et al , 2001b(Singh et al , 2001cCampbell et al 2002;Ji et al 2004;Lenihan et al 2005;Taboada-Gaytan et al 2009, 2010a, 2010bRohlfing et al 2010).…”
mentioning
confidence: 99%